Navigating the Integration of Blockchain Technology in Banking: Opportunities and Challenges - Hashimzai, Irshad Ahmed; Ahmadzai, Mohammad Zameer (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Integrating blockchain technology within the banking sector represents a pivotal transformation, promising enhanced security, transparency, and efficiency in financial operations. This qualitative research employs a systematic review approach to investigate the current state, challenges, and prospects of blockchain adoption in banking, drawing insights from a comprehensive analysis of scholarly literature. Through a systematic search and review of relevant academic journals, conference papers, books, and reports, this study explores critical variables such as security, transparency, efficiency, challenges, opportunities, and impact associated with blockchain adoption in banking. Thematic analysis is the primary methodological approach to identify recurring themes, patterns, and relationships across literature, facilitating a nuanced understanding of blockchain's implications for banking operations. The findings reveal a dual nature of blockchain adoption in banking, highlighting significant opportunities alongside critical challenges. While blockchain technology offers enhanced security, transparency, and efficiency, challenges like scalability issues, regulatory uncertainties, and interoperability concerns persist. Nonetheless, the study underscores the transformative potential of blockchain in revolutionizing banking operations, urging policymakers and banking practitioners to address these challenges through continued research, technological innovation, and collaborative efforts. By leveraging blockchain effectively, the banking industry can navigate the digital landscape, enhance operational efficiency, and deliver superior customer experiences, thereby gaining a competitive edge in the financial sector